Once Beaten, Never Again: Imitation in Two-Player Potential Games - Peter Duersch; Jörg Oechssler; Burkhard C. Schipper (University of Heidelberg, Department of Economics, 2012)
We show that in symmetric two-player exact potential games, the simple decision rule "imitate-if-better" cannot be beaten by any strategy in a repeated game by more than the maximal payoff difference of the one-period game. Our results apply to many interesting games including examples like 2x2 games, Cournot duopoly, price competition, public goods games, common pool resource games, and minimum effort coordination games.
urn:nbn:de:bsz:16-opus-134405
Keywords: D43; C73; C72; 330; Imitate-the-best; learning; exact potential games; symmetric games; relative payoffs; zero-sum games; Wiederholte Spiele; Lernprozess; Imitationsstrategie; Gemeingüter; Theorie